Readiness and exposure to information and communication technology instructional resources among pre-service teachers - Samson M. Lausa; Jick C. Balinario; Mary Ann T. Arceño (Journal of Pedagogical Research, 2024)
Readiness of teachers to use Information and Communication Technology [ICT] to teach is currently a major issue in the education system as it plays a significant role to teacher-learning continuity due to its relationship to flexible teaching/learning as the country's education response during pandemic. Preparing future teachers to use ICT to teach effectively to facilitate variety of learning modes is an enormous challenge for teacher training institutions. In this study, the ICT readiness of the 148 pre-service teachers in the College of Education was assessed. Quantitative design was used utilizing a validated and reliability tested researchers' made survey questionnaire. The data are analysed using frequency and percentage distribution, Mean, Mann-Whitney U test and Kruskal Wallis Test. Generally, the pre-service teachers are ready to use ICT to teach while access to ICT enabling environment and infrastructure at school is moderate. Likewise, pre-service teachers are exposed to ICT in teaching and have experience the pedagogical use of ICT in school and their field of placements and they gain confidence to integrate ICT in teaching-learning process. Finally, pre-service teachers consider technology integration as the future of teaching and learning that will change the landscape of the Philippine Education System towards achieving sustainable development goal 4 'Quality Education'.